THE USE OF MONDLY APPLICATION TO INCREASE SENIOR HIGH SCHOOL STUDENTS’ VOCABULARY MASTERY - Wardani, Ira; Lubis, Yani (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
Vocabulary is an important element in language learning that students have to master. English language learning is greatly influenced by technological advances. Several applications have provided more flexible and accessible means that can be used through smartphones as needed for vocabulary mastery . This study aims to find out how senior high school students can increase their vocabulary mastery through the use of Mondly. A quantitative approach with a pre-experimental design is the method used in this study. The 10th grade students of SMK Tritech Informatika Medan participated in the study.. According to the research findings, the students' mean score was 71.69 on the pretest and 83.53 on the posttest. The t-test with a sig (2-tailed) value of 0.000 or 0.05 was used to test the hypothesis. Therefore, "Ha" is accepted, and "Ho" is rejected. Thus, it can be concluded that vocabulary learned using Mondly application significantly increased the vocabulary mastery of tenth-grade students of SMK Tritech Informatika.Keywords: Vocabulary mastery, Mondly application, Language learning